Prognosis - Gordon, J. Jillq(Jennifer Jill); Macnaughton, Jane; Rudebeck, Carl Edvard (Medical humanities companion, 2014)
This fourth volume in the Companion to Medical Humanities series contemplates the challenge of the prognosis, of looking ahead, wondering what will happen, and attempting to make sense of life and death. Beautifully written, it encourages a positive view of life's unpredictability in all its richness, and considers, through personal and professional perspectives, the role of the medical profession in guiding patient experience. It offers inspirational reading for all academics and professionals with an interest in the medical humanities, as well as researchers in philosophy of medicine and medical ethics